We are moving (circular) - Jeger, George (1939)
042-0029-001 SPANISH MEDICAL AID COMMITTEE President: Rt. Hon. LORD ADDISON Vice-Presidents: Dr. CHARLES BROOK. L C.C. Dr. DAVID FORSYTH VICTOR GOLLANCZ Professor JULIAN HUXLEY Rt. Hon. Sir WILLIAM JOWITT. K.C. Sir WALTER T. LAYTON The EARL OF LISTOWEL Miss MEGAN LLOYD GEORGE, MP. TOM MANN D.N. PRITT. K.C. M.P. Miss ELEANOR RATHBONE. M.P. Miss ESTHER RICKARDS. L.C.C. JOS. ROBINSON, M.D. Dr. MAUDE ROYDEN Sir ARCHIBALD SINCLAIR. MP. BEN TILLETT Dr JANET VAUGHAN ALFRED M. WALL Miss REBECCA WEST Chairman : Dr. H.B. MORGAN. M.D. Vice-Chairman: Dr. SOMERVILLE HASTINGS, L.C.C. Treasurers: Viscountess HASTINGS Professor J.R. MARRACK Hon. Secretary: Mrs. LEAH MANNING, J.P. Organising Secretary: GEORGE JEGER, J.P. 24 NEW OXFORD STREET W.C.1 Telephone: HOLburn 1866 0605 WE ARE MOVING to 69 GREAT RUSSELL STREET W.C.1 (but our telephone number is the same) ON MARCH 29 Our old offices are being pulled down, but the work of the Committee is going on. We are still sending out to the Central Zone of Spain medical material and supplies of food - particularly medical foods - for the hospitals. In addition we are sending to the refugees in the Camps in France the most urgently needed requirements; medicaments, disinfectants and underclothing. We are also contributing towards the rescue of doctors from the Camps and their renewed start in life in a new land. The Spanish struggle is not over, and as long as it continues our place is wherever we are needed. The Spanish Medical Aid Committee was first in the field in August 1936, first to establish Relief Posts at the frontier in the evacuation, and there is still work to be done, our help is still needed. And we need your help, to enable us to ease the sufferings of these brave people, who after 33 months of war, are still unbroken in spirit. Sincerely yours, George Jeger Organising Secretary. 292/946/42/29